Internet literature in China - Hockx, Michel (Global Chinese culture., 2015)
Since the 1990s, Chinese literary enthusiasts have explored new spaces for creative expression online, giving rise to a modern genre that has transformed Chinese culture and society. Ranging from the self-consciously avant-garde to the pornographic, web-based writing has introduced innovative forms, themes, and practices into Chinese literature and its aesthetic traditions. This text describes in detail the types of Chinese literature taking shape right now online and their novel aesthetic, political, and ideological challenges.